Harnessing Human Intellect for Computing - Horvitz, Eric (Computing Research News, 2013)
The border between what computers and people are able do has been shifting over time. How might computers and people work together to solve difficult problems? In recent years, interest has been growing in the emerging interdisciplinary area of Human Computation, a field that explores principles and applications around giving computing systems programmatic access to human intellect to perform some aspect of computation, whether involving individuals or groups of people ("the vrowd").